2023
DOI: 10.5694/mja2.51920
|View full text |Cite
|
Sign up to set email alerts
|

A step in the right direction: the potential role of smartwatches in supporting chronic disease prevention in health care

Abstract: A step in the right direction: the potential role of smartwatches in supporting chronic disease prevention in health care Smartwatches can count every step towards a predict-prevent health care system, but clinical regulation is the first leap A ustralia is struggling with the ever-increasing burden of chronic disease. Over $38 billion per year is spent on care for people with chronic diseases, such as cardiovascular disease, type 2 diabetes, and cancer. 1 The majority of this funding is dedicated to acute ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In fact, a recent scoping review identified poor internet connectivity as a common problem in many digital health studies [64]. Therefore, to ensure the collection of medical-grade data that can be used in clinical practice, a concerted effort is needed by all stakeholders to remove any external barriers [65]. Especially considering the recent expanse of third-party developers and the wide range of smartwatches now available globally that will require standardised interoperability [46].…”
Section: Future Directionmentioning
confidence: 99%
“…In fact, a recent scoping review identified poor internet connectivity as a common problem in many digital health studies [64]. Therefore, to ensure the collection of medical-grade data that can be used in clinical practice, a concerted effort is needed by all stakeholders to remove any external barriers [65]. Especially considering the recent expanse of third-party developers and the wide range of smartwatches now available globally that will require standardised interoperability [46].…”
Section: Future Directionmentioning
confidence: 99%
“…Digital health technologies are revolutionising healthcare across primary, secondary and tertiary sectors, 31 and might have an increasingly larger role in supporting chronic disease prevention in healthcare. 32 Over 90% of Australians have a smartphone and the use of wearable technologies increased steadily from 28% of adults in 2020 to 58% in 2021. 33 e-Health interventions, such as web-based applications and software programs, are becoming more common in exercise care for chronic conditions.…”
Section: Ask and (Re)assess: Measuring And Monitoringmentioning
confidence: 99%